Jane's military review - Hogg, Ian V. (Jane's Publishing Company Limited, 1987)
In this sixth edition of Jane's military review we have, as usual, covered a wide field of subjects of military interest. As always, we would stress that the views of the contributors are entirely their own and where these contributors hold official posts their views do not necessarily reflect those of their employers. The military review is a forum for opinions, and there is no restraint upon them.